Convergent synthesis of oligomannose-type glycans via step-economical construction of branch structures. (March 2023) - Sano, Kanae; Ishii, Nozomi; Takahashi, Satoshi; Takeda, Yoichi; Matsuo, Ichiro
Abstract: Oligomannose-type glycans on glycoproteins are important signaling molecules in the glycoprotein quality control system in the endoplasmic reticulum. Recently, free oligomannose-type glycans generated by the hydrolysis of glycoproteins or dolichol pyrophosphate-linked oligosaccharides were recognized as important signals for immunogenicity. Hence, there is a high demand for pure oligomannose-type glycans for biochemical experiments; however, the chemical synthesis of glycans to achieve high-concentration products is laborious. In this study, we demonstrate a simple and efficient synthetic strategy for oligomannose-type glycans. Sequential regioselective α-mannosylation at the C-3 and C-6 positions of 2, 3, 4, 6-unprotected galactose residues in galactosylchitobiose derivatives was demonstrated. Subsequently, the inversion of the configuration of the two hydroxy groups at the C-2 and C-4 positions of the galactose moiety was successfully carried out. This synthetic route reduces the number of the protection–deprotection reactions and is suitable for constructing different branching patterns of oligomannose-type glycans, such as M9, M5A, and M5B. Graphical abstract: Image 1 Highlights: Convergent synthesis of oligomannosyl N -glycans Man5 or 9 GlcNAc2 was achieved. α(1–2) di-/tri-mannosyl donors from the self-coupling of thiomannoside were used. C-3/C-6 regioselective α-mannosylations to galactoside residue were demonstrated. β-mannoside in bulky branched glycan was successfully derived via the inversion reaction. Step-economical synthetic methodology of branched N -glycans was proposed.